Apple genotypes as pollen donors for Galaxy and Fuji Precoce cultivars under the organic cultivation system - Fioravanço, João Caetano; Soldatelli, Pâmella; Andolfato, William; Dias de Oliveira, Paulo Ricardo (Revista de Ciências Agroveterinárias, 2015)
Genotypes developed by breeding and ancestral apple cultivars with favorable phenological and productive features can be used in commercial orchards to improve pollination and extend the harvest period. In order to be suitable as a pollen donor in commercial orchards, the flowering time and compatibility with the commercial scions must be determined for the related pollen donors. The aim of this work was to investigate the phenology of 45 apple genotypes in comparison to the commercial cultivars Galaxy and Fuji Precoce. Time and extend of blooming are highly variable for the investigated genotypes. None of the investigated genotypes shows full coincidence (100%) of flowering period with the studied commercial scions. The coincidence of full blooming period with that of ‘Galaxy’ and ‘Fuji Precoce’ is better for ‘Pitchounette’, M-11/01, PA 14, ‘Florina’ and ‘Scarlett O’Hara’, which are considered the most promising pollen donors. The commercial scions Galaxy and Fuji Precoce exhibit excellent coincidence of full blooming period.